FAKTOR-FAKTOR YANG MEMPENGARUHI AKUNTABILITAS KINERJA ORGANISASI PERANGKAT DAERAH DAN INSTANSI PEMERINTAH KOTA PARIAMAN - Husna, Mutia Rahmatul; Yentifa, Armel; Rosalina, Eka (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This study intends to determine how the performance accountability of government agencies is influenced by budget target clarity, HR excellence, accounting controls, and reporting systems. Quantitative survey is the research technique used. The participants in this study were the head of the agency, the secretary, the treasurer in the revenue section and the treasurer in the expenditure section, as well as the finance subdivision that handles the accounting or financial tasks of each agency. With a total of 110 respondents, purposive sampling technique was used to conduct sampling. In this study, information was collected through questionnaires. SPSS v.25 program was used to process the data. Budget performance accountability is influenced by accounting controls, reporting systems and budget target clarity. Partially, the factors of government performance accountability are influenced by the clarity of budget targets, accounting controls and reporting systems in Pariaman City. Meanwhile, the quality factor of human resources has no effect on the performance accountability of government agencies in Pariaman City. Simultaneously, the accountability of Pariaman City government performance is also improved through budget target clarity, human resource excellence, accounting controls, and reporting systems.